Zakaz handlu w niedziele jako przejaw pozytywnej interwencji państwa w rynek. Ujęcie personalistyczne - Drobny, Paweł (Annales. Etyka w Życiu Gospodarczym, 2019)
The article is an attempt to look at the relationship between the state and the market on the example of the prohibition of trade on Sunday through the prism of the personalistic economy. The article has a metaeconomic character. Its aim is to show that state intervention in the market mechanism in the form of the prohibition of trade on Sunday is not aimed at trade as an economic activity, but is a natural consequence of the community-forming function of the state. In the first part, the author presents a personalistic approach to the state and the market as well as relations between them. In turn, in the second part, he describes the essence of the Sunday dispute in the context of a personalistic approach to the market and shows that state intervention, consisting in protecting Sunday from being limited to the seventh working day, protects it against rationalization and marketization, i.e. its derealization.